Analisis Perbandingan Teori Keadilan dan Teori Stakeholder dalam Menilai Tanggung Jawab Sosial Syariah Islam - Riri Sundari; Salwa Salwa; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to provide a comparative analysis of Justice Theory and Stakeholder Theory in assessing Islamic Sharia based social responsibility, particularly in the practices of Corporate Social Responsibility (CSR) and Islamic Social Reporting (ISR). The analysis is grounded in the conceptual divergence between a normative approach rooted in Islamic values of justice and an operational approach that prioritizes stakeholder interests. A qualitative method is employed through a comprehensive literature review of official Islamic banking reports, scholarly publications, and relevant prior studies. The findings indicate that Justice Theory emphasizes proportional distribution of benefits, vertical accountability to God, and the pursuit of maslahah as the fundamental objectives of Sharia-based economic activities, whereas Stakeholder Theory proves more adaptive in explaining corporate–stakeholder dynamics within modern business environments. However, the dominance of Stakeholder Theory without reinforcement of justice-based values risks reducing Islamic CSR to a mere instrument of legitimacy. Therefore, a synthesis of both theories is essential to construct a Sharia social responsibility framework that is equitable, operationally applicable, and sustainable.